MiR-101-3p and miR-106b-5p roles in EMT pathway: prognostic and therapeutic insights for luminal breast cancer - Gehad Tarek; Manar S. Fouda; Mohamed M. Omran; Gehan Safwat; Mahmoud M. Kamel; Abdel Hady A. Abdel Wahab (Journal of the Egyptian National Cancer Institute)
Abstract Introduction Breast cancer is considered to be the most common cancer that affects women worldwide, where it accounts for approximately 38.8% of all cancer cases among females. Luminal subtypes are the most prevalent in Egypt. Small noncoding RNAs also called microRNAs (miRNAs) influence gene expression posttranscriptionally. Since they regulate the epithelial-mesenchymal transition process, which is vital for tumor invasion and metastasis, microRNAs play a critical role in the progression of cancer. Methods This study has investigated the expression profiles of four microRNAs (miR-101-3p, miR-106a-5p, miR-106b-5p, and miR-130b-5p) and their impacts on genes associated with epithelial-mesenchymal transition (EMT) in luminal breast cancer. Tissue samples from 43 luminal breast cancer patients and 18 controls have been studied via real-time PCR (RT-qPCR). The association between the expression levels was evaluated using the Pearson correlation test. The correlation between the measured variables and numerous clinicopathological characteristics was assessed using the linear regression test. Results The results demonstrated that miR-101-3p, miR-106a-5p, and miR-106b-5p were significantly dysregulated, highlighting their possible role as oncogenes or tumor suppressors in the development of breast cancer. EMT markers, especially Twist, SNAI1, and E-cadherin, show significant alterations, indicating the activation of EMT pathways in luminal breast cancer. Correlation analysis showed interactions between miRNAs and EMT-related genes, showing a negative correlation between miR-101-3p and SNAI1, as well as a positive correlation between Twist and miR-106a-5p. Moreover, logistic regression analysis associated expression levels of those miRNAs with clinicopathological characteristics, such as body weight, age, and tumor laterality. Conclusion These findings highlight the leading role of miR-101-3p and miR-106b-5p in the progression of luminal breast cancer via interacting with the EMT process and their potential as diagnostic, prognostic, and therapeutic targets.